Migration of emboli in the retinal artery: case report. Issue 12 (19th November 2017) - Stepanov, Alexandr; Machackova, Marketa; Rehakova, Tereza; Jiraskova, Nada; Lestak, Jan
Key Clinical Message: Branch retinal artery occlusion (BRAO) is a prevalent vascular occlusive disorder of the eye. In transient BRAO, an embolus temporarily blocks the vessel and then moves on resulting in recovery of blood circulation. In this case, we have documented migration of the embolus with recovery of perfusion of the retina and improvement of visual acuity in a patient with transient BRAO. Early diagnosis and fast action are important in the case of patients with retinal artery occlusion. Abstract : Branch retinal artery occlusion (BRAO) is a prevalent vascular occlusive disorder of the eye. In transient BRAO, an embolus temporarily blocks the vessel and then moves on resulting in recovery of blood circulation. In this case, we have documented migration of the embolus with recovery of perfusion of the retina and improvement of visual acuity in a patient with transient BRAO. Early diagnosis and fast action are important in the case of patients with retinal artery occlusion.